Novel carbon dots/BiOBr nanocomposites with enhanced UV and visible light driven photocatalytic activity. Issue 39 (31st March 2015) - Du, Qingqing; Wang, Wenpeng; Wu, Yongzhong; Zhao, Gang; Ma, Fukun; Hao, Xiaopeng
Abstract : Novel CD/BiOBr nanocomposites were prepared and both UV and visible light photocatalytic activities were enhanced. Abstract : Novel UV and visible light photocatalytic carbon dots/BiOBr nanocomposites were prepared for the first time. The structures, morphologies, optical, photoelectrochemical and photocatalytic properties were investigated. The results indicated that the carbon dots (CDs) combined well with BiOBr. An appropriate amount of introduced CDs can significantly enhance the photocatalytic activities under both UV and visible light irradiation. The enhanced activities were mainly attributed to the enhanced light absorption and the interfacial transfer of photogenerated electrons. The corresponding photocatalytic mechanism was proposed based on the results.